ANALISA SISA KLOR DAN CANDIDA ALBICANS SERTA KELUHAN KESEHATAN MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN DI KOLAM RENANG SEJAHTERA CLUB CHAIN UNIVERSITAS NEGERI MEDAN TAHUN 2014 - isna desri yani; evi naria; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Swimming pool is one of the public places which is liked by all and a place where people can easily catch up with many disease. The joint use of swimming pool and poor hygiene can cause negative effects for health of the students from Faculty of Sport Sciences who regularly use the swimming pool of Sejahtera Club Chain, State University of Medan. Therefore, the quality of the pool water have to be monitored; chemical parameters such as residual chlorine (0.2-0.5 mg / L) and microbiological parameters such as the presence of Candida albicans (0/100ml water) in the pool water. The purpose of this research is to analyze the residual chlorine and Candida albicans in the pool water as well as the student’s health complaints after swimming in the pool. The type of research is a descriptive survey. The population in this study are students of the Faculty of Sport Sciences majors PJKR 2013 ledger as many as 173 students, with Taro Yamane formula obtained samples of 64 students. The research object, pool water, was taken at 5 points. The results shows that 85% pool sanitation is eligible, 15% is ineligible. Residual chlorine content of the test results obtained 0.024 mg / L to 0.033 mg / L is ineligible and positive Candida albicans was found in the pool water. Most health complaints associated is red eyes (81.3%) and scaly skin (56.25%). The research conclusion is ineligible residual chlorine and Candida albicans and occurs health complaints for swimmers. It is suggested to the manager of the swimming pool to do chlorine residual monitoring regularly. Keywords: Residual Chlorine, Candida albicans, Sanitation, Health Complaints